A-Site Doped in Perovskite La(1-x)Bax/2Srx/2Mn0.4Ti0.6O3 (x = 0, 0.1, and 0.3) for Absorbing Microwave Material - Saptari, Sitti Ahmiatri; Hapitanur, Dinda; Taryana, Yana; Sudrajat, Nanang; Rahman, Ikhwan Nur; Nanto, Dwi (Universitas Negeri Surabaya, 2023)
Microwave radiation can have harmful effects on our bodies. With increased exposure due to online activities, it is essential to use absorber materials like perovskite manganate to reduce radiation. In this study, perovskite manganate La(1-x)Bax/2Srx/2Mn0.4Ti0.6O3 (x = 0, 0.1, and 0.3) was synthesized using the sol-gel method. X-ray diffraction (XRD) analysis revealed that the two samples were multi-phased, LaMnO3 and La2Ti2O7, and were formed, exhibiting a rhombohedral crystal structure (R -3 c). Morphological characterization of the sample surface using a Scanning Electron Microscope (SEM) showed that as doping increases, the grain size decreases from 282.02 to 245.63 nm at x=0 and x=0.3, respectively. This result implies that doping leads to more uniform grain distribution and enhanced grain refinement. Characterization via Vibrating Sample Magnetometer (VSM) revealed that the maximum saturation value, 0.79 emu/g, was attained when x = 0. This sample exhibits soft magnetic properties, as evidenced by its coercivity (Hc) value of < 1kOe. Results from the Vector Network Analyzer (VNA) indicate that the absorption capacity of La(1-x)Bax/2Srx/2Mn0.4Ti0.6O3 increases, with a maximum reflection loss value of -25.5 dB with 1.5 mm thickness. Consequently, La(1-x)Bax/2Srx/2Mn0.4Ti0.6O3 demonstrates potential as a microwave absorber material.